Temperature variability and impact of vegetation cover in Ibadan metropolis, Ibadan, Nigeria (2021)
This study evaluates the changes in Urban Green Spaces (UGS) and the impact of such changes on surface temperature in Ibadan Metropolis between 1984 and 2018 using Landsat images. Digital numbers of the imageries were converted to physical quantities, radiance, and brightness temperature, while the temperature retrieval from thermal channels of Landsat imagery was carried out and the derived surface temperature validation was done through near-surface air temperature. This was followed by the reclassification of the images using Normalized Difference Vegetation Index (NDVI) as a proxy for vegetation cover and was regressed with urban temperature to observe their nexus, which explains the ability of UGS to absorb solar radiation in the study area. The land use land cover maps of the metropolis were developed from green, red and near-infrared channels of Landsat data in Idrisi software environment using maximum likelihood classifier. Results show that the mean temperature of Ibadan metropolis increased from 33.29℃ to 35.76℃ over 34 years, and the temperature of different land cover types considered in this study revealed that built-up and bare soil areas recorded the highest temperature changes compared to other land cover types (green spaces and water body). Also, the correlation analysis between UGS and ST showed a strong negative relationship with R2 values ranging from -0.71 to -0.89. The study, therefore, concludes that the relationship is strong enough to ascertain that urban vegetation cover has the capacity to mitigate climate change effects. The increase in temperature may contribute to the variations in surface temperature, thus giving rise to the urban heat island effect. The study revealed the efficiency of geospatial techniques in data capturing for reliable information on sustainable management of urban green spaces.